EDUKASI PEMANFAATAN DAUN KELOR SEBAGAI PRODUK OLAHAN BERNILAI GIZI DAN BERNILAI EKONOMI DI DESA ARJASA SITUBONDO - Elhany, Nurul Avidhah; Fajar, Muhammad Thoifur Ibnu; Suryaningsih, Yasmini; Suhesti, Endang; Untari, Wiwik Sri (Lembaga Penelitian dan Pengabdian kepada Masyarakat - Universitas Abdurachman Saleh Situbondo, 2024)
Moringa plants generally grow wild or are planted in the yard as a vegetable plant. The Moringa plant that is widely used by people is the leaf part. Moringa leaves are widely used as a vegetable because they can improve family nutrition. Apart from being used as a vegetable, Moringa leaves can also be processed into several Moringa leaf products. The service activities carried out in Arjasa village aim to utilize Moringa leaves by providing education on processing Moringa leaves for family nutrition and increasing family income. The service method is in the form of counseling about the benefits of Moringa leaves and an introduction to Moringa leaf preparations. From the results of service activities, participants can increase their insight and knowledge about the benefits of the Moringa plant and various types of processed products from the Moringa plant which can be used to improve family nutrition.